STRATEGI MENINGKATKAN KETERAMPILAN LITERASI MELALUI MEDIA PEMBELAJARAN POP UP BOOK DI KELAS IV SD MUHAMMADIYAH 2 PENDIL - Lutfiah, Nurika; Wahyuni, Sela; Fathoni, Anang (Journal of Professional Elementary Education, 2024)
Literacy skills are currently a special concern in the era of technological development because over time students no longer have an interest in literacy in reading texts. So in this case, relevant learning media are needed to attract their literacy interest. The solution to learning using media that attracts students' literacy interest is the creation of Pop Up Books. The purpose of the research conducted is to improve the literacy skills of fourth grade students of SD Muhammadiyah 2 Pendil through this media. Classroom Action Research (CAR) is a type of research chosen by researchers and is carried out in two cycles. The subjects of the study were 24 students in fourth grade. Learning outcome data were obtained through observation results of activities and tests in each cycle, which were then analyzed using descriptive statistics. The results of the study showed that there was an increase in learning outcomes of Pancasila norms in each cycle. The percentage of completion in cycle 1 was 62.5% and increased further in cycle 2 to 100%. The conclusion that can be drawn from this learning is that there is an increase in each cycle in learning outcomes of Pancasila norms using Pop Up Book media.